DIFFERENT METHODS FOR EVALUATING THE TRANSFER OF PASSIVE IMMUNITY IN BOVINE NEONATES - Casas, Bruno Alexandre Dombroski; Rodriguez, Giulia Ketllin Przywitowski; de Oliveira, Micaely Silva; Zeithammer, Natany; Rabassa, Viviane Rohrig; Gueretz, Juliano Santos; Peripolli, Vanessa; dos Santos, Betina Raquel Cunha; Moreira, Fabiana; Schwegler, Elizabeth (Seven Editora, 2026)
Considering that the syndesmochorial placenta prevents the transfer of immunoglobulins, the transfer of passive immunity is a determining factor for the success of the bovine neonate. This study aims to describe and compare direct and indirect diagnostic methods to optimize colostrum management and the transfer of passive immunity. To this end, the research technically analyzes the use of tools such as Radial Immunodiffusion (RID), Enzyme-Linked Immunosorbent Assay (ELISA), and Total Protein and Brix refractometry. Thus, the data reveal that digital refractometry offers high accuracy and practicality for rapid field monitoring. The use of this equipment allows for immediate adjustment in protocols, ensuring animal health and the financial return of the activity.